2020
DOI: 10.1111/bju.15265
|View full text |Cite
|
Sign up to set email alerts
|

Holmium laser enucleation of the prostate using Moses 2.0 vs non‐Moses: a randomised controlled trial

Abstract: To compare the enucleation efficiency of Moses 2.0 with non-Moses technology in patients undergoing holmium laser enucleation of the prostate (HoLEP). Patients and MethodsA double-blinded, randomised study of patients undergoing HoLEP at the Mayo Clinic in Arizona, using the Lumenis Pulse TM 120H laser system. Patients were randomised to either right lobe enucleation using Moses 2.0 and left lobe enucleation using non-Moses, or the opposite. The primary outcome was individual lobe enucleation efficiency. Secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 17 publications
(18 reference statements)
1
22
1
Order By: Relevance
“…Recent evidence suggests that MOSES-TM technology has further revolutionized HoLEP with modulated pulsed energy transmission (9). Enhanced energy delivery is believed to increase efficiency during HoLEP and reduce the operative and catheterization times, as well as blood loss (10). HoLEP performed using MOSES TM technology has been shown to provide faster hemostasis than HoLEP with a standard 100-W holmium laser (9).…”
mentioning
confidence: 99%
“…Recent evidence suggests that MOSES-TM technology has further revolutionized HoLEP with modulated pulsed energy transmission (9). Enhanced energy delivery is believed to increase efficiency during HoLEP and reduce the operative and catheterization times, as well as blood loss (10). HoLEP performed using MOSES TM technology has been shown to provide faster hemostasis than HoLEP with a standard 100-W holmium laser (9).…”
mentioning
confidence: 99%
“…13,14 Advancements in laser technology, such as the dual-pedal Lumenis 120H laser 15 and the Moses 2.0 upgrade have led to shorter times to achieve hemostasis and faster enucleation. 7,8 These clinical improvements translated to higher success rates with same-day discharges 16 and same-day catheter removals, 9 even for large glands !175 g. 10 Indeed, in one earlier series assessing the feasibility of outpatient HoLEP without Moses, the authors reported that of patients who were identified preoperatively as suitable for outpatient HoLEP, only 59.5% were able to be discharged. 17 The most common reason for failure of sameday discharge in that study was hematuria.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of HoLEP, the new version of pulse modulation technology results in improved hemostasis, decreased bleeding, faster enucleation times and therefore, possibly a shorter learning curve. 7,8 We have extensive experience with HoLEP at our institution; nevertheless, after adopting the routine use of Moses 2.0 we were able to consistently achieve same-day discharges and same-day catheter removals. 7,9 Similar excellent outcomes were shown in large prostates !175 cc with the use of Moses 2.0.…”
mentioning
confidence: 93%
“…Two more RCTs [37 ▪ ,38 ▪▪ ] compared Moses Technology for HoLEP vs. the standard laser technology. The first one shares a limited sample size (n = 27) and a peculiar design, where each patient was treated with both Moses Technology and standard HoLEP [37 ▪ ], randomizing thus the prostatic lobe to be treated rather than patients themsevels. The second one [38 ▪▪ ] has a more conventional study design, and demostrates shorter operative (68 vs. 80 min, P = 0.03) and hemostasis time (mean: 18 vs. 29 min, P < 0.01) with M-HoLEP, although standard HoLEP patients had larger prostate size (153 vs. 131 g).…”
Section: Evidence Synthesismentioning
confidence: 99%